2016
DOI: 10.4196/kjpp.2016.20.3.305
|View full text |Cite
|
Sign up to set email alerts
|

NecroX-5 exerts anti-inflammatory and anti-fibrotic effects via modulation of the TNFα/Dcn/TGFβ1/Smad2 pathway in hypoxia/reoxygenation-treated rat hearts

Abstract: Inflammatory and fibrotic responses are accelerated during the reperfusion period, and excessive fibrosis and inflammation contribute to cardiac malfunction. NecroX compounds have been shown to protect the liver and heart from ischemia-reperfusion injury. The aim of this study was to further define the role and mechanism of action of NecroX-5 in regulating infl ammation and fi brosis responses in a model of hypoxia/reoxygenation (HR). We utilized HR-treated rat hearts and lipopolysaccharide (LPS)-treated H9C2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 67 publications
1
17
0
1
Order By: Relevance
“…The SNPs in certain genes, for example, IRS1 , endothelin receptor type A ( EDNRA ), DCN , and ZFHX3 , are frequently associated with CVD or related traits, including our study. Insulin signaling and function was shown to reduce atherosclerosis through the endothelin receptors, whereas downregulation of DCN and ZFHX3 were associated with anti‐inflammatory/antiapoptotic and perturbed Ca2 + homeostasis, respectively . Functional studies are available for a few but future research is needed to ascertain the separate or combined effects of these genes that have been consistently associated with CVEs.…”
Section: Discussionmentioning
confidence: 99%
“…The SNPs in certain genes, for example, IRS1 , endothelin receptor type A ( EDNRA ), DCN , and ZFHX3 , are frequently associated with CVD or related traits, including our study. Insulin signaling and function was shown to reduce atherosclerosis through the endothelin receptors, whereas downregulation of DCN and ZFHX3 were associated with anti‐inflammatory/antiapoptotic and perturbed Ca2 + homeostasis, respectively . Functional studies are available for a few but future research is needed to ascertain the separate or combined effects of these genes that have been consistently associated with CVEs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, antioxidants and anti-inflammatory agents have been applied to suppress the cellular effects of ischemia [20]. Recently, anti-necrotic effects of NecroX-5 on IRI have been evaluated in the murine heart and canine liver IRI models [8]. NecroX-5 strongly prevented myocardial damage in ischemic heart disorders by preventing mitochondrial dysfunction [8].…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvement in the protection of cell and tissue has been showed against various injury factors, such as neomycin, nitroprusside, oxidative stress, and gentamicin [5][6][7]. Recently, the fundamental role of NecroX-5 in IRI in the heart and liver has been described, however, there has been no research to determine the molecular mechanisms underlying the inhibition of NecroX-5 in IRI [8,9]. The goal of this research was to investigate the therapeutic efficiency and its underlying mechanism of NecroX-5 on the IRI in rat flap model.…”
Section: Original Articlementioning
confidence: 99%
“…TGFβ1 is of great significance in various pathological processes, including infarction, myocardial remodeling and interstitial fibrosis (30). An analysis of TGFβ1 and SMAD2 levels and their correlation with CHD risk factors indicated that TGFβ1 is associated with the expression of lipoprotein A and uric acid (31,32). Increased levels of lipoprotein A and uric acid are considered as markers of atherosclerosis, which indicates that TGFβ1 may regulate atherosclerosis, thereby accelerating the establishment of CHD.…”
Section: Discussionmentioning
confidence: 99%